Efektivitas Penggunaan Ringer Laktat Vs Ringer Asetat terhadap Durasi Rawat Inap Pasien Demam Berdarah Dengue - Erwin Ari Pratiwi; Eko Retnowati; Intan Adevia Rosnarita (Pusat Riset dan Inovasi Nasional, 2025)
Dengue hemorrhagic fever (DHF) is an endemic disease with high prevalence in Indonesia, particularly during the rainy season, when incidence rates significantly increase. One of the main treatments is supportive therapy through intravenous fluid administration to prevent shock and aid recovery. Ringer’s lactate and Ringer’s acetate are commonly used crystalloid fluids that differ in electrolyte composition and metabolic pathways in the body. This study aimed to compare the effectiveness of Ringer’s lactate and Ringer’s acetate in relation to the length of hospital stay among DHF patients. This research employed a retrospective analytic observational design, using data from medical records of 154 inpatients at RSUD dr. R. Soetrasno Rembang in 2024. Data analysis included normality testing and independent t-tests. The average length of hospitalization in the Ringer’s lactate group was 4.35 ± 1.121 days, while in the Ringer’s acetate group it was 4.06 ± 1.185 days. Although there was a difference in mean values, statistical analysis showed no significant difference between the two groups (p = 0.131). No significant differences were also found in laboratory parameters (platelets, leukocytes, hemoglobin, hematocrit) or body temperature. Based on these findings, it can be concluded that both types of fluids are equally effective as supportive therapy for DHF patients. Fluid selection may be adjusted according to the patient’s clinical condition, availability, and cost considerations.